CALD1 is a prognostic biomarker and correlated with immune infiltrates in gastric cancers. Issue 6 (June 2021) - Liu, Yixuan; Xie, Suhong; Zhu, Keyu; Guan, Xiaolin; Guo, Lin; Lu, Renquan
Abstract: Background: Caldesmon gene (CALD1) plays an important role in many cellular functions. Some researchers have found the correlation between CALD1 expression and prognosis of gastrointestinal cancer (GI), but the association with tumor-infiltrating lymphocytes (TILs) still unclear. Methods: The expression of CALD1 in different human tumor was analyzed by Oncomine and Tumor Immune Estimation Resource (TIMER) databases. The correlations between CALD1 and prognosis in types cancer were explored by Kaplan–Meier plotter and Gene Expression Profiling Interactive Analysis (GEPIA) databases. The association between CALD1 expression and tumor immune cell infiltration was further analyzed via TIMER and GEPIA databases. Results: The CALD1 expressions in types cancer between tumor tissues and adjacent normal tissues were significantly different. The high expression of CALD1 was related with poor overall survival (OS) of patients with gastric cancer, especially in gastric cancer patients at N1, N2 and N3 stages. The expression of CALD1 was positively associated with immune-infiltrated, such as CD8+T cells, CD4+T cells, macrophages, neutrophils, and dendritic cells (DCs) in gastric cancer. Conclusions: CALD1 was considerably a key role in prognosis of patients with gastric cancer. The expression level of CALD1 is significantly associated with immune-infiltrated in gastric cancer. Furthermore, CALD1 expression may be involved in regulating tumor-associated macrophages (TAMs), dendritic cells, exhausted T cells and regulatory T cells in gastric cancer. These findings suggest that CALD1 could be utilized as a marker of prognosis and immune infiltration in gastric cancer. Highlights: CALD1 plays an important role in immune infiltration in gastric cancer. CALD1 can affect the prognosis in gastric cancer patients with lymph node metastasis. CALD1 plays a vital role in immune escape in the gastric cancer microenvironment. Abstract : CALD1, immune infiltration, gastric cancer, microenvironment